Studies in behavioural epidemiology - Flisher, Alan John (Department of Psychiatry and Mental Health, 2017)
Collection of papers submitted to the Faculty of Medicine, University of Cape Town, in fulfilment of the requirements of Part III of the Degree Master of Medicine in Psychiatry.